Successful Surgical Treatment of an Infected Thoracoabdominal Aneurysm Accompanied with Leriche Syndrome. (21st April 2019) - Furui, Masato; Hirata, Hirohisa; Kakii, Bunpachi; Uchino, Gaku; Asanuma, Mai; Suzuki, Haruo; Nishioka, Hiroaki; Yoshida, Takeshi
Abstract : A 56-year-old man presenting with massive melena and loss of consciousness was diagnosed with an infected thoracoabdominal aneurysm, an aortoduodenal fistula, and Leriche syndrome following an evaluation by computed tomography. Emergency surgery for uncontrolled infection included the reconstruction of the superior mesenteric and bilateral renal arteries using a four-branched graft. The aortoduodenal fistula was resected after omental filling, and an enterostomy was performed for feeding. Intestinal reconstruction was performed in two stages. The patient was discharged on postoperative day 48 and was without evidence of recurrence at 23 months postoperatively.